Bactericidal action mechanism of negatively charged food grade clove oil nanoemulsions. (15th April 2016) - Majeed, Hamid; Liu, Fei; Hategekimana, Joseph; Sharif, Hafiz Rizwan; Qi, Jing; Ali, Barkat; Bian, Yuan-Yuan; Ma, Jianguo; Yokoyama, Wallace; Zhong, Fang
Highlights: Food grade clove oil (CO) nanoemulsion of 150 nm size with purity gum ultra (PGU) was prepared. PGU nanoemulsion showed strong antimicrobial activity against Gram positive bacterial strains. Bactericidal mechanism was not associated with the charge of surfactant. Abstract: Clove oil (CO) anionic nanoemulsions were prepared with varying ratios of CO to canola oil (CA), emulsified and stabilized with purity gum ultra (PGU), a newly developed succinylated waxy maize starch. Interfacial tension measurements showed that CO acted as a co-surfactant and there was a gradual decrease in interfacial tension which favored the formation of small droplet sizes on homogenization until a critical limit (5:5% v/v CO:CA) was reached. Antimicrobial activity of the negatively charged CO nanoemulsion was determined against Gram positive GPB ( Listeria monocytogenes and Staphylococcus aureus ) and Gram negative GNB ( Escherichia coli ) bacterial strains using minimum inhibitory concentration (MIC) and a time kill dynamic method. Negatively charged PGU emulsified CO nanoemulsion showed prolonged antibacterial activities against Gram positive bacterial strains. We concluded that negatively charged CO nanoemulsion droplets self-assemble with GPB cell membrane, and facilitated interaction with cellular components of bacteria. Moreover, no electrostatic interaction existed between negatively charged droplets and the GPB membrane.